Strategy Management STRATEGIC MANAGEMENT TO IMPROVE THE QUALITY OF EDUCATION IN THE DIGITAL ERA (Case Study at SMA Negeri 15 Surabaya) - Wilujeng Ardana Neswari, Widantining Tyas (LPPM of NAROTAMA UNIVERSITY, 2025)
Education in the digital era presents new challenges and opportunities for education management. This article discusses educational strategy management that can be used to improve the quality of education in the digital era. This study uses a descriptive qualitative method with data collection in the form of interviews, documentation, and observation. This article describes several educational management strategies that can be applied, including the use of digital technology in teaching and learning, human resource management in the digital era, curriculum development that is relevant to technology, and the application of learning models that are appropriate to the digital era. This article also discusses the challenges and opportunities faced in implementing these strategies, including change management, adaptive education policies, and teacher professional development in the digital era. This research was conducted at SMA Negeri 15 Surabaya where the subjects of the study were the principal or vice principal, curriculum field, and economic education teachers . In the digital era, adaptive and technology-oriented educational management strategies are the key to improving the quality of education. The use of digital technology in teaching and learning, human resource management oriented to the digital era, curriculum development that is relevant to technology, and the application of learning models that are in accordance with the digital era are steps that can be taken to improve the quality of education in the digital era. However, challenges such as change management, adaptive education policies, and teacher professional development remain important focuses in the implementation of these strategies.